EFFECT AIRCRAFT EXHAUST GASES ON SUM OF GREEN-HOUSE ATMOSPHERE GASES - Božidarka Arsenović; Zoran Janjuš; Emil Banjac (Journal of Engineering & Processing Management, 2012)
Global Warming Potential - GWP is an agreed quantity which enables determination of an individual green-house gas effect on a global warming process. GWP quantity illustrates how a unit mass of an observed gas contributes to increase of global warming more than an unique mass of CO2, during certain period of time. The paper shows gases and substances resulted from combustion of aircraft engine fuel , so as their affect to the atmosphere. The paper is a short view of an ecological aspect of aeronautics contibution to climate changes, as well as to results of green-house gas emission.
Keywords: global warming; green-house gases; aeronautics